2017
DOI: 10.1111/age.12568
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Syrian Arabian horses

Abstract: Although Arabian horses have been bred in strains for centuries and pedigrees have been recorded in studbooks, to date, little is known about the genetic diversity within and between these strains. In this study, we tested if the three main strains of Syrian Arabian horses descend from three founders as suggested by the studbook. We examined 48 horses representing Saglawi (n = 18), Kahlawi (n = 16) and Hamdani (n = 14) strains using the Equine SNP70K BeadChip. For comparison, an additional 24 Arabian horses fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…However, those populations went through a severe male bottleneck, as our panel originates from only 26 imported stallions. According to several studies, registered Arabian horses in the Middle East show expanded genetic and phenotypic diversity in comparison to the global Arabian bloodlines [ 27 , 49 , 50 , 51 ]. The existence of genetically diverse populations of Arabian horses in the Middle East today could also be reflected in more diverse MSY patterns.…”
Section: Resultsmentioning
confidence: 99%
“…However, those populations went through a severe male bottleneck, as our panel originates from only 26 imported stallions. According to several studies, registered Arabian horses in the Middle East show expanded genetic and phenotypic diversity in comparison to the global Arabian bloodlines [ 27 , 49 , 50 , 51 ]. The existence of genetically diverse populations of Arabian horses in the Middle East today could also be reflected in more diverse MSY patterns.…”
Section: Resultsmentioning
confidence: 99%
“…In the last two centuries, the so-called “Arabian wave” has profoundly influenced the selective breeding practices of European horses [ 19 ], but no genetic signatures were found in the English Thoroughbred’s MSY ancestry [ 126 ]. A particular genetic variability was found among the Arabian stallions from the Middle East [ 29 , 84 , 126 , 146 ], thus suggesting an origin from this area for this breed.…”
Section: The Horse Y Chromosome’s Variationmentioning
confidence: 99%
“…Recently, many studies have been focused on the loss of biodiversity [ 23 , 24 , 25 ] or the increase in deleterious genotypes [ 26 ] caused by such inbreeding (as reviewed in [ 7 ]). In the last 200 years, the inbreeding practice led to the phenotypical expression at homozygous sites of deleterious variants [ 27 ], as highlighted when the coefficients are calculated in order to evaluate the genetic diversity among different horse breeds [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ,…”
Section: Introductionmentioning
confidence: 99%
“…Sadeghi et al [ 29 ] delved into the genetic diversity in 71 Arabian horses and reported H e and H o values of 0.45 and 0.43, respectively. Furthermore, Almarzook et al [ 30 ] employed genome-wide SNP data to investigate Syrian Arab horse breeds, discovering average H e and H o values ranging between 0.30–0.31 and 0.30–0.32, respectively. These findings suggest that a diminished level of heterozygosity in this horse breed might be a consequence of intense artificial selection targeting economically significant phenotypic traits or the isolation of populations that could have led to a reduced gene flow, leading to a loss of genetic diversity [ 28 ].…”
Section: Discussionmentioning
confidence: 99%